2021
DOI: 10.1175/jtech-d-20-0086.1
|View full text |Cite
|
Sign up to set email alerts
|

Land Surface Temperature from GOES-East and GOES-West

Abstract: Land surface temperature (LST) is an important climate parameter that controls the surface energy budget. For climate applications, information is needed at global scale with representation of the diurnal cycle. To achieve global coverage there is a need to merge about five independent geostationary satellites (GEO) that have different observing capabilities. An issue of practical importance is the merging of independent satellite observations in areas of overlap. An optimal approach in such areas could elimin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 90 publications
0
1
0
Order By: Relevance
“…With an advancements of new generation geostationary satellites, such as Himawari-8, Geostationary Operational Environmental Satellite R-Series (GOES-R), Geostationary Korea Multi-Purpose Satellite-2A (GEO-KOMPSAT-2A), and FengYun-4A, possibility to monitor sub-daily GPP is increasing (e.g., Bessho et al, 2016;Wang et al, 2020). The optical sensors on these satellites have been added multiple solar reflective and thermal infrared bands and improved spatiotemporal resolution, enabling them to provide land surface parameters such as downwelling shortwave radiation (SRd), vegetation indices, and land surface temperature (LST) that are useful for estimating sub-daily GPP (Cheng et al, 2020;Chen et al, 2021). Xiao et al (2021) demonstrated that a semi-empirical light use efficiency (LUE) model driven by the Himawari-8 data has a possibility to represent the variation in diurnal GPP due to a heatwave at one site in Australia.…”
Section: Introductionmentioning
confidence: 99%
“…With an advancements of new generation geostationary satellites, such as Himawari-8, Geostationary Operational Environmental Satellite R-Series (GOES-R), Geostationary Korea Multi-Purpose Satellite-2A (GEO-KOMPSAT-2A), and FengYun-4A, possibility to monitor sub-daily GPP is increasing (e.g., Bessho et al, 2016;Wang et al, 2020). The optical sensors on these satellites have been added multiple solar reflective and thermal infrared bands and improved spatiotemporal resolution, enabling them to provide land surface parameters such as downwelling shortwave radiation (SRd), vegetation indices, and land surface temperature (LST) that are useful for estimating sub-daily GPP (Cheng et al, 2020;Chen et al, 2021). Xiao et al (2021) demonstrated that a semi-empirical light use efficiency (LUE) model driven by the Himawari-8 data has a possibility to represent the variation in diurnal GPP due to a heatwave at one site in Australia.…”
Section: Introductionmentioning
confidence: 99%